Inefficacy of a Highly Selective T‐Type Calcium Channel Blocker in Preventing Atrial Fibrillation Related Remodeling. (30th January 2014) - KATO, TAKESHI; IWASAKI, YU‐KI; DUKER, GORAN; FJELLSTROM, OLA; GIORDANETTO, FABRIZIO; SUNDQVIST, MONIKA; WALLIN, ANITA; WANG, QING‐DONG; NATTEL, STANLEY
Effects of T‐Type Calcium Channel Blockade on AF: Background: The T‐type Ca 2+ channel (ICaT ) blocker mibefradil prevents AF‐promoting remodeling occurring with atrial tachycardia, an action that has been attributed to ICaT inhibition. However, mibefradil has other effects, including ability to inhibit L‐type Ca 2+ channels, Na + channels and cytochromes. Thus, the relationship between ICaT inhibition and remodeling protection in AF is still unknown. Objective: To assess the effects of a novel highly selective Cav3 (ICaT ) blocker, AZ9112, on atrial remodeling induced by 1‐week atrial tachypacing (AT‐P) in dogs. Methods: Mongrel dogs were subjected to AT‐P at 400 bpm for 7 days, with atrioventricular‐node ablation and right‐ventricular demand pacing (80 bpm) to control ventricular rate. Four groups of dogs were studied in investigator‐blinded fashion: (1) a sham group, instrumented but without tachypacing or drug therapy (n = 5); (2) a placebo group, tachypaced but receiving placebo (n = 6); (3) a positive control tachypacing group receiving mibefradil (n = 6); and (4) a test drug group, subjected to tachypacing during oral treatment with AZ9112 (n = 8). Results: One‐week AT‐P decreased atrial effective refractory period (ERP) at 6 of 8 sites and diminished rate‐dependent atrial ERP abbreviation. Mibefradil eliminated AT‐P‐induced ERP‐abbreviation at 4 of these 6 sites, while AZ9112 failed to affect ERP at any. Neither drug significantly affected AF vulnerability or AF duration. Conclusions: ICaT blockade with the highly selective compound AZ9112 failed to prevent rate‐related atrial remodeling. Thus, prevention of atrial electrophysiological remodeling by mibefradil cannot be attributed exclusively to ICaT blockade. These results indicate that ICaT inhibition is not likely to be a useful approach for AF therapy.